OPTICAL SUBSCRIBER NETWORK (2011)
An optical subscriber network for power reduction is provided. The optical subscriber network may include an Optical Line Terminal (OLT) and an Optical Network Terminal (ONT). The OLT may manage a plurality of ONTs by classifying the plurality of ONTs into a sleep group, and may multicast a sleep allowance message only to ONTs included in a predetermined sleep group.